Evaluation of Tall Fescue Cultivars - J. L. Moyer (Kansas Agricultural Experiment Station Research Reports, 2018)
Tall fescue (Lolium arundinaceumSchreb.) is the most widely grown forage grass in southeastern Kansas. Its tolerance to extremes in climate and soils of the region is partly attributable to its association with a fungal endophyte,Neotyphodium coenophialum; however, most ubiquitous endophytes are also responsible for production of substances toxic to some herbivores, including cattle, sheep, and horses. Endophytes that purportedly lack toxins, but augment plant vigor have been identified and inserted into tall fescue cultivars adapted to the United States. These cultivars, and others that are fungus-free or contain a ubiquitous endophyte (i.e. Ky 31 EF and HE, respectively) are included in this test.
Keywords: forage production; endophyte